2013
DOI: 10.1149/2.104306jes
|View full text |Cite
|
Sign up to set email alerts
|

Alkanethiols as Inhibitors for the Atmospheric Corrosion of Copper Induced by Formic Acid: Effect of Chain Length

Abstract: Self assembled monolayers (SAMs) of n-alkanethiols of different chain length (4,6,8,12, and 18 carbons in the chain) have been explored as corrosion inhibitors for copper exposed to humidified air containing formic acid, an environment used to mimic accelerated indoor atmospheric corrosion. Near-surface sensitive in-situ infrared reflection/absorption spectroscopy combined with interface sensitive vibrational sum frequency spectroscopy revealed unique molecular information on the role of each SAM during ongoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 34 publications
2
37
0
Order By: Relevance
“…For example, Laibinis and Whitesides 3 reported that alkanethiols adsorbed on copper surface are effective inhibitors of atmospheric copper corrosion. It was also demonstrated that alkanethiols inhibit atmospheric corrosion of copper, zinc and Cu-Zn alloys induced by formic acid, [4][5][6][7] as well as corrosion in aqueous solutions. [8][9][10][11] Due to the strong binding between sulfur and copper atoms, alkanethiol SAMs formed on nonoxidized copper surface have better protective properties compared to those formed on copper oxides.…”
mentioning
confidence: 99%
“…For example, Laibinis and Whitesides 3 reported that alkanethiols adsorbed on copper surface are effective inhibitors of atmospheric copper corrosion. It was also demonstrated that alkanethiols inhibit atmospheric corrosion of copper, zinc and Cu-Zn alloys induced by formic acid, [4][5][6][7] as well as corrosion in aqueous solutions. [8][9][10][11] Due to the strong binding between sulfur and copper atoms, alkanethiol SAMs formed on nonoxidized copper surface have better protective properties compared to those formed on copper oxides.…”
mentioning
confidence: 99%
“…Another reason is that the penetration of the corrosion stimulators, water (H 2 O), formic acid (HCOOH) and oxygen gas (O 2 ) in our case, through the self-assembled monolayer occurs slower for longer alkyl chain lengths. 19 However, even for ODT, the corrosion protection gradually decreases with increasing exposure time, and over a similar time scale the conformational order in the adsorbed ODT layer decreases. 24 A major aim of this study is to explore the potential of ODT as a corrosion inhibitor on zinc and on Zn-Cu patterned samples.…”
mentioning
confidence: 99%
“…Another reason is that the penetration of the corrosion stimulators, water (H 2 O), formic acid (HCOOH) and oxygen gas (O 2 ) in our case, through the self-assembled monolayer occurs slower for longer alkyl chain lengths. 19 However, even for ODT, the corrosion protection gradually decreases with increasing * Electrochemical Society Active Member.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is a challenge to follow the formation of extremely thin corrosion layers (a few monolayers to ∼1 nm) on copper surfaces in real-time in ambient environments even using current state of the art characterization techniques, and new sensitive methods are desirable. Many studies have focused on rather aggressive environments such as (air-saturated) salt solutions, 9,11,12,15 air with high humidity and traces of other oxidants, 3,13,19 or elevated temperature (>150 • C) 14 where signals are relatively high and easier to measure. Few studies are available for mildly corrosive ambient environments: Laibinis et al 7 studied the oxidation of Cu protected by various nalkylthiols at ∼20 • C and <30% relative humidity (RH) using X-ray photoelectron spectroscopy (XPS), Jennings et al 8 at ∼20 • C and ∼10% and 100% RH using XPS and contact angle measurements, and Hutt et al 16 at 20-25 • C and ∼50% RH, ∼4 • C and ∼50% RH, as well as −30 • C using XPS.…”
mentioning
confidence: 99%